The effects of microenergy acoustic pulses on an animal model of obesity‐associated stress urinary incontinence. Part 1: Functional and histologic studies. Issue 8 (4th September 2019) - Wang, Bohan; Ruan, Yajun; Zhou, Tie; Wang, Lin; Li, Huixi; Peng, Dongyi; Reed‐Maldonado, Amanda B.; Sanford, Melissa T; Lee, Yung‐chin; Zhou, Jun; Wang, Hsun Shuan; Banie, Lia; et al.
Abstract: Aim: Obesity is a strong independent risk factor for urinary incontinence. Effective therapeutic approaches for obesity‐associated stress urinary incontinence (OA‐SUI) are lacking as the mechanisms remain unclear. The aim of our study is to explore the impacts of microenergy acoustic pulse (MAP) therapy on urethral and pelvic floor muscle structure and function in female lean and fatty rats. Methods: A total 24 Zucker fatty (ZF) and 24 Zucker lean (ZL) female 24‐week‐old rats were grouped into four groups: ZL control, ZLMAP, ZF control, and ZFMAP. For MAP treatment, 500 pulses were delivered at an energy level of 0.033 mJ/mm 2 and a frequency of 3 Hz and were applied twice a week for 4 weeks. After a 1‐week washout, all rats underwent conscious cystometry and leak‐point pressure (LPP) measurements followed by ex vivo organ‐bath assay and histological study. Results: ZF rats had lower LPP as compared to ZL rats, and MAP treatment significantly improved LPP in ZF rats ( P < .05). Impaired muscle contractile activity (MCA) in organ‐bath study was noted in ZF rats. MAP treatment significantly increased MCA in ZF rats ( P < .05) and also increased the thickness of the striated muscle layer and the number of neuromuscular junctions (NMJs). In situ, MAP activated muscle satellite cells significantly ( P < .05). Conclusions: Obesity impairs the function of both the urethral sphincter and the pelvic floor and leads to atrophy and distortion of the striated muscle in obese female rats. These issues contribute to OA‐SUI. MAP improves continence by stimulating muscle regeneration and nerve innervation as well as by activating satellite cells.